Salik Buta: Aliran Tasawuf Aceh Abad XX - Muchsin, Misri A (Al-Jamiah Research Centre, 2004)
This article examines the Sufi movement in Aceh by looking at its continuity since the 16th -17th century, as its golden age, to the 20th century. Based on the fact that Abdullah Ujong Rimbas explanation is considered representative, his books are taken as primary sources while others are secondary. Based on Abdullah Ujong Rimbas explanation, Salik Buta is a sect of Sufism in Aceh in the 20th century. This sect is practiced in several of center in Aceh. Historically, the doctrine of this sects is continuation and modification of Wahá¸at al-WujÅ«dsÂ doctrines established since 16th century. The doctrine of Salik Buta are different from those of popular Sufism. Thus, Salik Buta is considered heterodox and criticized by ulama, as Abdullah Ujong Rimba. From Abdullah Ujong RImbas criticism, it can be conclude that his thought based on syariat or Fiqih orientation, instead of the perspective of Sufism.